Taxonomia de Eiphosoma Cresson, 1865 (Hymenoptera: Ichneumonidae: Cremastinae) do Brasil - Sousa, Ana Flávia Avelino (Entomologia, 2022)
Eiphosoma Cresson, 1865 (Hymenoptera: Ichneumonidae) comprises a total 56 species valid, most of them neotropics and currently has 23 records for Brazil. Most species occur in open environments, even degraded, and in agroecossystems, where they act as natural controllers of populations of other insects, especially Lepidoptera larvae. Although they are relatively common in several environments, the taxonomy of this group was poorly explored in the country. Thus, the objective of this study was to identify, describe and redescribe Eiphosoma species in Brazil. The material studied was obtained from national zoological collections and the Amazon Biodiversity of Insects Project (REDEBIA). Fourteen species of Eiphosoma were identified that already had records for Brazil (four of them were redescribed and one revalidated), 15 species were registered for the first time in the country and six new species were described, totaling 35 species. Besides that, the states of Roraima, Acre, Rondonia, Tocantins, Piaui and Ceara had the genus registered for the first time. All species studied have an identification key and maps with geographic records.